2022
DOI: 10.1021/acsnano.2c07263
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Self-Assembly of Nonplanar Molecules with Aggregation-Induced Emission Characteristics

Abstract: Utilizing nonplanar conjugated molecules as building blocks facilitates the development of self-assembly but is fundamentally challenging. To study the self-assembly behavior, we herein demonstrate the self-assembly process of a nonplanar conjugated molecule with aggregation-induced emission (AIE) feature from an isolated molecule to an irregular cluster to a well-defined vesicle driven by amphiphiles. The superhigh aggregation-sensitive emission affords more precise and detailed information about the self-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The crystalline aggregates of three amphiphiles show an obvious discrepancy in their emission intensity and wavelength, suggesting the diverse arrangement tightness and configuration of TPE core within their aggregates. [ 40 ] As shown in Figure 2I, an emission peak centered at 457 nm was observed for TO2C aggregates, whereas a strong and a large red‐shifted emission peak at about 484 nm for TO6C aggregates, and a weaker emission centered at about 470 nm for T2OE aggregates. The difference in emission intensity of aggregates formed under the same concentration indicates the arrangement tightness of three amphiphiles inside decreases in the order of TO6C > TO2C > T2OE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystalline aggregates of three amphiphiles show an obvious discrepancy in their emission intensity and wavelength, suggesting the diverse arrangement tightness and configuration of TPE core within their aggregates. [ 40 ] As shown in Figure 2I, an emission peak centered at 457 nm was observed for TO2C aggregates, whereas a strong and a large red‐shifted emission peak at about 484 nm for TO6C aggregates, and a weaker emission centered at about 470 nm for T2OE aggregates. The difference in emission intensity of aggregates formed under the same concentration indicates the arrangement tightness of three amphiphiles inside decreases in the order of TO6C > TO2C > T2OE.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, three amphiphiles adjust themselves to take a different twisted conformation to fit into their surrounding environment, giving rise to diverse emission wavelength in their respective monomeric and aggregated states. [36,40,42]…”
Section: The Photophysical and Self-assembly Propertiesmentioning
confidence: 99%
“…This excitation can induce a range of vibrational modes from membrane fluctuations in the MHz frequency regime to thickness vibrations in the GHz frequency regime. 40,41 Femtosecond transient absorption spectroscopy is a widely used technique for investigating high-frequency acoustic vibrations in metal nanoparticles. 42−44 Typically, metal nanoparticles are supported by a substrate for spectroscopy measurements.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…During the transformation process, AIE active molecules are arranged from disordered to ordered aggregates by noncovalent driving forces in polar solution, proving that the strong hydrophobicity of amphiphilic compounds plays a crucial role in conformational and morphological changes. 16 Guo et al reported a novel strategy for constructing polyelectrolyte assemblies based on AIE dyes, which exhibit excellent photothermal conversion efficiency in aqueous solution. 17 DSA, as a typical AIE structure, is favored by researchers due to its simple structure and ease of synthesis.…”
Section: ■ Introductionmentioning
confidence: 99%